Against consensus: Embracing the disunity of personality theory. (1st January 2020) - Matthews, Gerald
Abstract: Theories of personality traits refer to qualitatively different explanatory mechanisms, limiting prospects for a consensual paradigm. This article presents a trilevel cognitive science analysis that distinguishes multiple, qualitatively different explanations for expressions of personality. Stable individual differences in processes and content associated with traits are distributed within and between levels of explanations. A unitary and coherent account of traits is thus problematic. The Cognitive-Adaptive Theory of Traits (CATT) provides a conceptual framework that inter-relates theories at different levels, and identifies trait coherence with individual differences in strategies for managing adaptive goals. It exemplifies a spirit of explanatory pluralism that accepts disunity in personality theory. That is, it is preferable to work with multiple, conceptually rigorous theories at different levels than to aim for a universal paradigm prematurely.